Exosome-encapsulated miRNAs contribute to CXCL12/CXCR4-induced liver metastasis of colorectal cancer by enhancing M2 polarization of macrophages. (1st April 2020) - Wang, Dong; Wang, Xiaohui; Si, Mahan; Yang, Juan; Sun, Shiyue; Wu, Haochen; Cui, Shuxiang; Qu, Xianjun; Yu, Xinfeng
Abstract: Tumor-associated macrophages (TAMs) are important immunocytes associated with cancer metastasis. However, whether TAMs play a dominant role in mediating CXCL12/CXCR4-induced liver metastasis of colorectal cancer (CRC) remains unexplored. Herein, we found that CD206 + TAMs, which infiltrated at the invasive front, were correlated with CXCR4 expression and liver metastasis of CRC in clinical specimens. Several miRNAs (miR-25-3p, miR-130b-3p, miR-425-5p), upregulated in CRC cells by activation of the CXCL12/CXCR4 axis, could be transferred to macrophages via exosomes. These exosomal miRNAs induced M2 polarization of macrophages by regulating PTEN through activation of PI3K/Akt signaling pathway. In turn, M2 polarized macrophages promoted cancer metastasis by enhancing epithelial-mesenchymal transition (EMT) and secreting vascular endothelial growth factor (VEGF). Co-culture of CRC cells with macrophages transfected with these miRNAs or treated with exosomes enhanced their metastatic capacity both in vitro and in vivo . Clinically, the serum levels of exosomal miR-25-3p, miR-130b-3p and miR-425-5p were correlated with progression and metastasis of CRC. In conclusion, these results reveal a crucial role of exosomal miRNAs in mediating the crosstalk between CXCR4 overexpressing cancer cells and TAMs, providing potential therapeutic targets for circumventing liver metastasis of CRC. Highlights: CD206 + TAMs were correlated with CXCR4 expression and liver metastasis of colorectal cancer. Exosomal miR-25, miR-130b, miR-425 induce macrophage M2 polarization via PTEN/PI3K/Akt pathway. M2 polarized macrophages promote cancer metastasis by enhancing EMT and secreting VEGF. Exosomal miR-25, miR-130b and miR-425 levels in serum were associated with progression of CRC.